2020
DOI: 10.13189/ujer.2020.080441
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Reflection-for-Action in Planning English Language Lesson at Primary School

Abstract: Teaching English language is a challenging task for p rimary school teachers. Teachers need to plan their lesson to match all levels of students in one class as there is no streaming classes allowed. This study exp lored how reflection-for-action to be used by the English language teachers at primary schools in Northern state of Peninsular Malaysia in planning their teaching starting fro m choosing lesson objectives, planning the activities and preparing the materials. Hence, this study also gathered another r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In relation to the first aspect of the research, the results portrayed that the teachers applied reflective practice to adjust and make changes to plan the lesson, during teaching and after teaching to reframe their teaching for future lesson [9,36,45]. Similar to Sua, et al [17] as well as Lee [36], the teachers in this study claimed that reflective activities support them to be more progressive and enable them to increase their teaching quality [2][3][4][5] but, the findings showed that, rather than practicing reflective practice on their own, the teachers need ample support from the school administration to improve their practices in schools [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In relation to the first aspect of the research, the results portrayed that the teachers applied reflective practice to adjust and make changes to plan the lesson, during teaching and after teaching to reframe their teaching for future lesson [9,36,45]. Similar to Sua, et al [17] as well as Lee [36], the teachers in this study claimed that reflective activities support them to be more progressive and enable them to increase their teaching quality [2][3][4][5] but, the findings showed that, rather than practicing reflective practice on their own, the teachers need ample support from the school administration to improve their practices in schools [17].…”
Section: Discussionmentioning
confidence: 99%
“…The support and collaborative reflective activities [23] will motivate the teachers in implementing reflective activities in their teaching and learning process which could ease the teachers' stress in providing effective teaching [5,43] to increase students' learning performance and to fulfil the pedagogical, content and context demands [5,14] based on their own pace and significant to the context as suggested by Jejo and Haji [24]. It is because well motivated teachers play their role meaningfully to convey their enthusiasm to their students [4,31,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improving the effectiveness of English lessons in primary school, by strengthening the informational, communicative and emotional saturation of the educational process, is an urgent need of leading modern methodists (Flynn [82], Goh and Fang [83], Hashim and Yusoff [84], Järvinen and Twyford [85], Niyazova and Muratova [86], Pokorna [87], Reid [88], Xu et al [89]).…”
Section: Requirements For Professional Competence Of Primary School T...mentioning
confidence: 99%